Enhancing luminescence of Lu2MoO6:Eu3+ phosphors by doping with Li+ ions for near ultraviolet based solid state lighting. (June 2016) - Li, Li; Shen, Jun; Pan, Yu; Zhou, Xianju; Huang, He; Chang, Wenxuan; He, Qiwei; Wei, Xiantao
Graphical abstract: The emission spectra of Lu2 MoO6 :3%Eu 3+, x%Li + phosphors under 365 nm excitation. The inset represents emission intensity of 610 nm as a function of Li + molar concentration. Highlights: Lu2 MoO6 :3%Eu 3+, x%Li + phosphors were synthesized by solid-state reaction method. All the prepared phosphors can be assigned to its monoclinic phase. The optimal concentration of Li + ions is 30mol%. The luminescent intensity of Lu2 MoO6 :Eu 3+ phosphors has been greatly enhanced by codoping Li + ions. Abstract: Lu2 MoO6 : 3% Eu 3+ co-doped with x% Li + ( x  = 0–40 mol) phosphors were synthesized by high-temperature solid-state reaction method. The structure and luminescent properties of these phosphors were investigated. The X-ray diffraction (XRD) results show that all prepared phosphors can be assigned to monoclinic phase and codoping with Li + ions does not change their crystallographic structure. The excitation and emission spectra show that the samples can be effectively excited by the near ultraviolet light at 365 nm and exhibit strong red emission centered at 610 nm. The experimental results indicate the red luminescent intensity of Lu2 MoO6 :Eu 3+ phosphors has been greatly enhanced by codoping with Li + ions. The enhancement of the luminescent intensity can be the consequence of the modification of the local field symmetry around the Eu 3+ ion, improved crystallization, and the enlarged grain size induced by the Li + ions.